Physical Education Teachers’ Knowledge of Physical Activity Recommendations for Health Promotion in Children and Adolescents - De Moraes-Ferrari, G (Nature Research, 2023)
This study aimed to analyse the knowledge of Portuguese physical education (PE) teachers according to the health recommendations for physical activity (PA) for children and adolescents. A total of 764 teachers participated (55.2% men) with a mean age of 48.2 years. Data was collected using answering to an online survey. Teachers were asked about PA’s frequency, duration and intensity to achieve the recommended level PA. Chi-square was applied to analyse the associations. The main finding is that PE teachers have a lack of knowledge of the health recommendations of PA. Specifically, only 7.5% of the PE teachers in our study could identify the PA recommendations correctly. The intensity component in the health recommendation is the one in which most PE teachers demonstrate correct knowledge of (60.5%), with significant differences in gender and teaching level. However, significantly fewer PE teachers knew the frequency component in the health recommendations for PA (25%), with significant differences in education level. For the duration component, only 37.6% of teachers knew the recommendations. In light of our findings, it is a concern that PE teachers generally lack knowledge according to children’s fulfilment of health recommendations for PA. © 2023, The Author(s).